Design and Analysis of Finger Prosthetics Using Finite Element Methods - Agisna, Faza; Kumarajati, Dhananjaya Yama Hudha; Nur’aidha, Amalia Cemara (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
According to the Central Statistics Agency (BPS), the total number of physically disabled people in Indonesia until 2020 reached 22.5 million people. However, only around 18% use assistive devices. 3D printing technology in the world of health can be used to print prosthetic materials. However, many previous functional prosthetic designs were still fabricated conventionally and did not pay attention to prosthetic standards and quality. One computational testing method that can be used to test prosthetic strength is the finite element method. The aim of this research is to produce a functional finger prosthetic design that has tested its strength through computational simulations using the finite element method to minimize prosthetic production costs so that the resulting prosthetics are more affordable.The tools needed in this research are a ruler for finger measurements and a computer or laptop with Fusion 360 software.Based on the analysis results, it shows that this model is able to withstand loads of up to 100 N with deformation, stress and safety factor values produced respectively of 0.016 mm, 27,605 MPa and 7.49.